Commercial Real Estate Valuation Using CoStar - Margarita Kaprielyan; Angelo Boone (Journal of Real Estate Practice and Education)
This paper presents a structured property investment evaluation project for real estate finance courses utilizing CoStar database. Grounded in cognitive load theory, collaborative learning, and Hattie and Timperley’s feedback model, the project employs a scaffolded approach to manage cognitive load, foster peer engagement, and incorporate iterative feedback to deepen learning. Students begin with a comparative market analysis and progress through multiple stages, ultimately selecting a property, conducting submarket analysis, and applying financial analysis techniques such as DCF and IRR based on their findings. Student survey results indicate that the project enhances hands-on experience with CoStar, connects theory with application, strengthens understanding of real estate market analysis, builds skills in DCF and financial analysis, and develops competency in data interpretation for informed investment decisions. The scaffolded design also supports the effective incorporation of instructor feedback, as evidenced by student responses.